Deformation twinning versus slip in Ni-based alloys, containing Pt2Mo-structured, Ni2Cr-typed precipitates. (September 2021) - Vo, H.T.; Dang, K.; Teng, F.; Schneider, M.; Eftink, B.P.; Maloy, S.A.; Tucker, J.D.; Capolungo, L.; Hosemann, P.
Graphical abstract: Highlights: The molecular dynamics and crystallographic analysis showed that the activation of slip versus twinning is governed by one type of interaction and the Schmid factors of the dislocation partials. Coupled with transmission electron microscopy, micropillar compression provided direct observation of the grain orientation effect on the activation of slip versus twinning due to Pt2 Mo-structured, Ni2 Cr-typed precipitates. Molecular dynamics revealed a novel twin formation mechanism from an energy-based approach. Abstract: Nickel-based alloys are extensively used in a wide range of extreme environments because of their exceptional mechanical properties. The excellent strength of these alloys is derived from the addition of long-range ordered precipitates, introduced by thermal aging. The interactions between the dislocations and LRO precipitates dictate the deformation modes and plastic response in these alloys. While the majority of studies have focused on L12 -structured precipitate-strengthened Ni-based alloys, less work has considered the Ni-based alloys containing Pt2 Mo-structured, Ni2 (Cr, Mo)-typed precipitates. In these alloys, Pt2 Mo-structured precipitates enable room-temperature deformation twinning in addition to slip, which increases strain hardenability measured from bulk mechanical testing. Although previous geometric-based model suggested that deformation twinning is favored over slip, the factors that influence the activation between twinning versus slip have not been thoroughly explored in this class of Ni-based alloys. In this work, molecular dynamics examined the possible types of dislocation and Pt2 Mo-structured precipitate interactions at low temperature. Combined with in situ micromechanical testing, the role of resolved shear stresses on dislocation partials were shown to directly influence the activation of slip versus twinning. Additionally, using an energy-based approach, molecular dynamics results demonstrated a novel twin formation process, caused by the dislocation interaction with the Pt2 Mo-structured precipitates.